Influence of hydrocracking and ionic liquid pretreatments on composition and properties of Arabidopsis thaliana wild type and CAD mutant lignins - Jacquet, Nicolas; Eudes, Aymerick; Dutta, Tanmoy; Kim, Kwang Ho; Bouxin, Florent; Benites, Veronica; Baidoo, Edward; Singh, Seema; Simmons, Blake; Loque, Dominique; Richel, Aurore (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Lignin is the primary contributor to the high cost of biofuel-production from lignocellulosic biomass. In order to study lignin removal and the release of aromatic monomers, we applied hydrocracking and ionic liquid pretreatments on Arabidopsis thaliana biomass from both wild type (WT) and a mutant (CAD cxd) defective in two cinnamyl alcohol dehydrogenase genes involved in the lignin biosynthetic pathway. For Arabidopsis WT, our results highlight that pretreatments reduce average molecular weight of lignin by about 65% and decrease the content of beta-O-4 linkages between lignin monomers. For Arabidopsis CAD mutant, an opposite effect is evidenced. Fewer differences were observed on depolymerization and molecular structure of lignin, which indicates that (8-O-4), (8-5), and (8-8) linkages observed in CAD mutant make lignin more resilient to pretreatment than wild-type lignin. Finally, our study shows the potential of hydrocracking pretreatment technology for extracting valuable aldehyde monomers such as vanillin and syringaldehyde from biomass. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: FERMENTABLE SUGAR YIELDS; PLANT-CELL WALLS; ETHANOL-PRODUCTION; MOLECULAR-WEIGHT; BIOSYNTHESIS; BIOMASS; SORGHUM; MAIZE